The discovery of a second species of Mallophthiria Edwards (Diptera, Bombyliidae, Crocidiinae) from Chile - Yamaguchi, Carolina; Lamas, Carlos José Einicker (Zootaxa, 2014)
The Neotropical genus Mallophthiria Edwards is restricted to Chile (Concepción and Choapa) and comprises M. lanata Edwards, 1930 and M. elguetai sp. nov. The new species is described and illustrations of the external morphology of adults and male and female terminalia are also included.